PRAGMATIC FUNCTIONS OF INTENSIFIERS IN ENGLISH AND UZBEK MEDIA TEXTS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article examines the pragmatic functions of intensifiers in English and Uzbek media texts, focusing on how lexical and phraseological means are used to strengthen meaning, guide interpretation, and influence audience perception. Intensifiers such as scalar adverbs, extreme adjectives, reduplication, evaluative expressions, and emotionally loaded phraseological units are analyzed within their communicative contexts. The study reveals that English media typically employs controlled, graded forms of intensification to shape evaluative tone subtly, while Uzbek media relies more heavily on expressive and culturally embedded intensifiers to create emotional resonance. By comparing these patterns, the research highlights how linguistic structure, cultural norms, and media strategies determine the pragmatic roles of intensifiers in shaping stance, persuasion, dramatization, and ideological framing.